Fang : a Maximum Ride novel - Patterson, James, 1947- (Little, Brown, 2010)
When Max and the Flock discover an unscrupulous scientist who is experimenting on humans in an effort to "improve" the human race, they decide that they must try to stop him, in spite of Angel's prediction about Fang dying.